The application of lean technologies to optimize oncological screening in the periodic health examination of adult population groups - A. A. Komanenko; M. V. Avdeeva; T. Yu. Garifullin; V. N. Filatov (Acta Biomedica Scientifica, 2021)
Background. Improving organizational technologies for early detection of cancer using targeted programs for large-scale cancer screening is a priority task of primary health care.The aim: to assess the potential of lean technologies to optimize cancer screening during periodic health examination of the adult population.Materials and methods. To develop an optimal organizational and functional model of cancer screening, a working group was created; information about the current state of the process was collected.Results. A comprehensive analysis of the state of the process revealed the following problems: violation of the algorithms of oncological screening at stage 1 of periodic health examination (13.8 %); cases of non-completion of stage 2 of periodic health examination by patients with suspected colon cancer (20.4 %); queues for endoscopic examinations (14 days) and, as a consequence, not a quick visit to the oncologist of the primary oncology department (17–18 days). After optimization of the periodic health examination: there is no queue for endoscopy for patients with suspected oncopathology; accelerated access of patients with suspected oncopathology to the oncologist of the primary oncology department (from 17–18 to 5 days; p < 0.01). Increased awareness of patients about the rules for preparing for endoscopic examination and a reminder of the date and time of the upcoming endoscopy, there was an increase in the number of patients who completed stage 2 of health examination to exclude/confirm oncopathology (from 79.6 to 90 %; p < 0.05). The frequency of violations by doctors of the oncological screening algorithm decreased from 13.8 to 2.3 % (p < 0.01).Conclusion. The use of lean manufacturing marketing strategies in primary health care has helped to identify, eliminate and control the causes of problems during the first and second stages of clinical examination of patients with suspected oncopathology.